Gymnastic skills on a balance beam with simulated height - Ritter, Y.; Bürger, D.; Pastel, S.; Sprich, M.; Lück, T.; Hacke, M.; Stucke, C.; Witte, K. (Human Movement Science, 2023)
Virtual reality (VR) is a valuable tool for simulating dangerous situations and training under these conditions with a reduced possibility of injury. This could be beneficial within different sports scenarios. In gymnastics, the height of the balance beam can be dangerous and frightening, especially for beginners. Here, a simulated height can reduce the participant's risk of injury and facilitate entry to balance beam gymnastics. However, the investigation of sports performance in a virtual environment is rare. Therefore, the current study aims to compare beginners' performance in balance beam tasks between the real world (RW) and VR. 34 sports students executed gymnastic balancing forward, backward and the extension of one leg to the front, the side and the back on a regular balance beam in the RW and on a balance beam with simulated height in VR (using a head-mounted display). We analyzed beginners' performance in both conditions (RW and VR) regarding different criteria for each balance beam task. Statistical analyses show significant differences in performance with better results in RW (p < .05). Especially the body tension and the upper body posture were superior in RW. One explanation can be the more difficult regulation of the balance in VR. For the tasks where the motion took part in a fixed position on the beam, the further performance aspects were similar for RW and VR. When the participants moved along the beam, further performance aspects, like the leg extension, were better in RW. In total, the participants executed the VR balance beam tasks with decreased danger of injury due to the simulated height of the balance beam, but their performance was slightly limited. We conclude that for the first contact with the height of a balance beam, VR is a suitable tool to reduce the danger of injury occurring from falling off the beam and facilitate entry to balance beam gymnastics.